2007
DOI: 10.1097/opx.0b013e318031b649
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Habitual Refractive Errors and Headache Complaints in Schoolchildren

Abstract: Habitual RE and headache complaints are relatively common conditions in schoolchildren aged between 11 and 13 years. Headache complaints showed a small but statistically significant association with the sphere component of habitual RE in girls and the cylinder component of habitual RE in boys. The associations found between habitual RE and headache complaints indicate that habitual RE might be a risk factor for headache in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 28 publications
3
29
0
Order By: Relevance
“…Headache complaints showed a small but statistically significant association with the sphere component of refractive error in girls and the cylinder component of refractive error in boys. 9 On the basis of our study, we conclude that compound and mixed types of astigmatism, anisometropia, and miscorrection of refractive error are found more often in patients with headache than in control subjects.…”
Section: Discussionmentioning
confidence: 86%
“…Headache complaints showed a small but statistically significant association with the sphere component of refractive error in girls and the cylinder component of refractive error in boys. 9 On the basis of our study, we conclude that compound and mixed types of astigmatism, anisometropia, and miscorrection of refractive error are found more often in patients with headache than in control subjects.…”
Section: Discussionmentioning
confidence: 86%
“…found a higher prevalence of astigmatism in the group with headache, whereas spherical refractive errors were not significantly different between groups. Hendricks et al ., in a study of 487 children also found a weak but significant association between headache and habitual (i.e. uncorrected) astigmatic refractive error, but only in boys.…”
Section: Visual and Functional Impact Of Astigmatismmentioning
confidence: 90%
“…Recent studies have observed that some children have higher grades of dehydration by the time they arrive at school 21,22,100 which could have considerable consequences on cognition, 22,101,102 headache and refractive errors. 103,104 This could suggest that at school and intensive study, children do not hydrate sufficiently and could have an effect over the long term on their myopia. On the other hand, outdoors activities and especially during the summer would tend to encourage the consumption of fluids, mainly water, and thus could have the protective effect on myopia.…”
Section: Refractive Errormentioning
confidence: 99%